2022
DOI: 10.1158/1078-0432.ccr-22-1125
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy Is Associated with Altered Immune Cell Infiltration and an Anti-Tumorigenic Microenvironment in Resected Pancreatic Cancer

Abstract: Purpose: Neoadjuvant chemotherapy is increasingly administered to patients with resectable or borderline resectable pancreatic ductal adenocarcinoma (PDAC), yet its impact on the tumor immune microenvironment is incompletely understood. Experimental design: We employed quantitative, spatially-resolved multiplex immunofluorescence and digital image analysis to identify T-cell subpopulations, macrophage polarization states and myeloid cell subpopulations in a multi-institution cohort of up-front resected primary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Although our dataset lacks deep spatial characterization some of the broad features raised in our scRNAseq analyses are recapitulated in our multiplex IHC/IF analysis. To date some of the correlations between inferred network structure from scRNAseq and ground truth analysis such as IHC and IF and emerging spatial transcriptomics appear to largely hold, which is reassuring for our data 9,10,38,62,63,72,73 . As we needed to prioritize patient safety, our serial samples are limited to endoscopic biopsies of the primary tumor and we recognize the potential value for complementary spatial transcriptomics approaches.…”
Section: Discussionsupporting
confidence: 57%
“…Although our dataset lacks deep spatial characterization some of the broad features raised in our scRNAseq analyses are recapitulated in our multiplex IHC/IF analysis. To date some of the correlations between inferred network structure from scRNAseq and ground truth analysis such as IHC and IF and emerging spatial transcriptomics appear to largely hold, which is reassuring for our data 9,10,38,62,63,72,73 . As we needed to prioritize patient safety, our serial samples are limited to endoscopic biopsies of the primary tumor and we recognize the potential value for complementary spatial transcriptomics approaches.…”
Section: Discussionsupporting
confidence: 57%
“…Additionally, our biological conclusions on impacts of αCD40 are concordant with several prior studies (8, 14, 72, 73, 77, 79, 80, 83), providing further support for our methods and findings. Future antibody panels may incorporate additional markers, such as chemokine receptors, to further characterize key T cell subsets, or additional cell lineage markers, such as myeloid cell markers (89), to further phenotype cell-cell interactions. It should be noted that in our study, treatment with αCD40 did not prolong DFS as compared to the treatment-naive cohort, and similar machine learning analyses on data from clinical trials that did improve outcome will be useful to validate our conclusions where the patient cohort size is better powered for survival analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitatively, numerous studies demonstrated that neoadjuvant chemotherapy could elevate cytotoxic lymphatic cell (i.e., CD8+ T cells, conventional CD4+ T cells, and NK cells) and decline immunosuppressive myeloid cells (M2-skewed cells and myeloid-derived suppressor cells) infiltration, creating an anti-tumorigenic microenvironment [10,26,28,29] and a tendency to reverse natural tumor progression in pancreatic cancer.…”
Section: Reshaped Tumor Immune Cells In Quantity Space and Functionmentioning
confidence: 99%
“…Spatial distribution of cytotoxic CD8 T cells in proximity to cancer cells correlates with increased overall patient survival [31]. M1-polarized macrophages were located closer to tumor cells after neoadjuvant chemotherapy, and colocalization of M1-polarized macrophages and tumor cells was associated with greater tumor pathologic responses and improved patient survival [29]. Okubo et al [32] demonstrated that CD204+ macrophage levels in the cancer stroma were similarly independent of chemotherapy, whereas those in the cancer cell nests were lower in the treated group than in the naïve group.…”
Section: Reshaped Tumor Immune Cells In Quantity Space and Functionmentioning
confidence: 99%
See 1 more Smart Citation